Changes in the size of cephalic salivary glands of Apis mellifera and Scaptotrigona postica (Hymenoptera: Apidae) queens and workers in different life phases - Poiani, Silvana B. [UNESP]; Cruz-Landim, Carminda da [UNESP] (Sociedade Brasileira de Zoologia, 2010)
The bee species of the Apinae, in addition to the thoracic salivary glands, possess a pair of cephalic glands originating as branches of the excretory duct that crosses the head. These glands are known as cephalic salivary or labial cephalic glands. The degree of development of these glands in newly emerged, nurse and forager workers and virgin and egg-laying queens of Apis mellifera Linnaeus, 1758 and Scaptotrigona postica Latreille, 1807 were evaluated by measuring the secretory alveolar units. The area of the secretory alveoli, measured in total gland preparations, was used to evaluate differences in size. In both species, gland size was found to increase progressively from newly emerged workers to foragers and from virgin to egg-laying queens. A statistical analysis revealed significant differences (p < 0.05) in the area of gland alveoli of workers in different life phases in both species, and between S. postica virgin and egg-laying queens, but not between A. mellifera queens. In the case of workers, this suggests cephalic salivary gland secretion has a function in forager activity and, in queens, a possible pheromonal function.
Keywords: Bee; labial gland; morphometry; pheromone; salivary system